PENGARUH KEMAMPUAN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KARYAWAN PADA BKPSDM KOTA MALANG (Magister Manajemen Universitas Wisnuwardhana, 2022)
This study aims to determine and analyze the influence of work ability and work experience of employees through work motivation at the Agency for Personnel and Human Resources Development in Malang City. The mediating variable is the influence of work ability on employee performance through work motivation and the effect of work experience on employee performance through work motivation. The population in this study were all employees who worked at the Agency for Personnel and Human Resources Development (BKPSDM) Malang City which found 47 people. The sampling technique used in this study used a purposive sampling technique. The data used in this study is primary data from the results of questionnaires. The method in this research is the validity and reliability test, Classical Assumptions which consists of normality test and multicollinearity test. The analytical tool in this study uses Path Analysis with the SPSS for Windows version 22 program. The results showed that the direct effect of using three variables, namely work ability, work experience and work motivation had a positive and significant effect on employee performance. While the indirect effect uses two variables, namely work ability and work experience, which has a positive and significant effect on work motivation. Then the mediating variable, namely work motivation affects work ability and work experience on employee performance.